If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -11 = 2(x + -3) + -8 Reorder the terms: -11 + 3x = 2(x + -3) + -8 Reorder the terms: -11 + 3x = 2(-3 + x) + -8 -11 + 3x = (-3 * 2 + x * 2) + -8 -11 + 3x = (-6 + 2x) + -8 Reorder the terms: -11 + 3x = -6 + -8 + 2x Combine like terms: -6 + -8 = -14 -11 + 3x = -14 + 2x Solving -11 + 3x = -14 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -11 + 3x + -2x = -14 + 2x + -2x Combine like terms: 3x + -2x = 1x -11 + 1x = -14 + 2x + -2x Combine like terms: 2x + -2x = 0 -11 + 1x = -14 + 0 -11 + 1x = -14 Add '11' to each side of the equation. -11 + 11 + 1x = -14 + 11 Combine like terms: -11 + 11 = 0 0 + 1x = -14 + 11 1x = -14 + 11 Combine like terms: -14 + 11 = -3 1x = -3 Divide each side by '1'. x = -3 Simplifying x = -3
| -26+17= | | 1=-3xy | | 4t+5=2 | | 3(1-2x)=6-6x | | 16+-12+-7= | | x^2+X(c-b)+(c-a)(a-b)=0 | | 4x-90=3x-60 | | 5x+3y=56 | | abc-cba=973 | | -9x+1=-26 | | abc-cba=891 | | 4*sinx*cosx+2*cosx+1=0 | | abc-cba=675 | | 3a+7+2a=18-9 | | abc-cba=456 | | 15z-75=180 | | x-11=4x+44 | | 6(x-3)=2(3x-5) | | 4t-66=5t-87 | | sin(2x)+2*cosx+1=0 | | X^4-x^3-27x^2+25x+50=0 | | 4(5x-3)=2x-34 | | 8q-67=6q-35 | | 3(c+5)=2(c+3)-11 | | 3q-132=180 | | sen(2x)+2*cosx+1=0 | | 6s-90=180 | | x+11=2(3x-2) | | 6w-54=3w | | x=320x | | 8.1a+12=93 | | 4.2+3.4= |